2015
DOI: 10.3354/aei00141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the metabolism, behaviour and oxygen requirements of Sparus aurata

Abstract: There is currently little information on the sea cage O 2 levels in S. aurata aquaculture, but variation in the above mentioned factors is expected to cause variable levels of O 2 in S. aurata production systems as well. In order to develop production strategies ABSTRACT: We investigated the effect of temperature on the limiting oxygen saturation (LOS) of gilthead sea bream Sparus aurata. This threshold was defined as the % O 2 saturation where fish no longer upheld their routine metabolic rate (RMR, the metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…The overall focal observations indicate that the chronic stress protocol dramatically reduced fish group activity. This is in accordance with various previous studies, which also demonstrated a decrease in locomotor activity in different fish species exposed to hypoxic conditions (goldfish ( Carassius auratus ): Israeli and Kimmel, 1996; Atlantic cod ( Gadus morhua ): Herbert and Steffensen, 2005; rainbow trout: Steffensen and Farrell, 1998; sea bream ( Sparus aurata ): Remen et al, 2015). If locomotor activity represents a complex and situation-specific pattern, any visual increase or decrease of the swimming activity in tanks can be easily observed by fish farmers and thus would represent a relevant indicator of impaired welfare.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The overall focal observations indicate that the chronic stress protocol dramatically reduced fish group activity. This is in accordance with various previous studies, which also demonstrated a decrease in locomotor activity in different fish species exposed to hypoxic conditions (goldfish ( Carassius auratus ): Israeli and Kimmel, 1996; Atlantic cod ( Gadus morhua ): Herbert and Steffensen, 2005; rainbow trout: Steffensen and Farrell, 1998; sea bream ( Sparus aurata ): Remen et al, 2015). If locomotor activity represents a complex and situation-specific pattern, any visual increase or decrease of the swimming activity in tanks can be easily observed by fish farmers and thus would represent a relevant indicator of impaired welfare.…”
Section: Discussionsupporting
confidence: 93%
“…This inhibited human avoidance in the chronically stressed fish possibly reflects global apathy, a common expression of poor welfare as described above (Boissy et al, 2001). This might also be linked to the decrease in swimming activity previously observed in various fish species exposed to hypoxia conditions (Steffensen and Farrell, 1998; Remen et al, 2015).…”
Section: Discussionmentioning
confidence: 79%
“…The oxygen consumption level is one parameter to understand the fish metabolism rate and the oxygen consumption level is affected by the water temperature (Remen et al, 2015). Table 2 showed that the increasing of water temperature (22-30°C) was followed by the increasing of oxygen consumption level in elver.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, if these covariates are not collected at the time of survey as is often the case, they need to be found as records elsewhere, or modeled using an appropriate method. Temperature, for example, is known to affect the metabolism and behavior of marine fish (Biro, Beckmann, & Stamps, ; Remen et al., ), which can affect the detection probability. Including temperature in the hydrodynamic model used in the current study can only be achieved by specifying water densities as a function of temperature and salinity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, if these covariates are not collected at the time of survey as is often the case, they need to be found as records elsewhere, or modeled using an appropriate method. Temperature, for example, is known to affect the metabolism and behavior of marine fish (Biro, Beckmann, & Stamps, 2010;Remen et al, 2015), which can affect the detection probability. Including temperature in the hy- forecasting these types of data may not be a viable option for many researchers planning future studies, it is a recommendation of this study that an effort be made to consider the fine-scale variability of any feature of the environment that may impede detection of their target species.…”
Section: Recommendations For Future Studiesmentioning
confidence: 99%